TREATMENT OUTCOMES OF URETERAL STONES IN ELDERLY PATIENTS USING URETEROSCOPIC LITHOTRIPSYAT THONG NHAT HOSPITAL, HO CHI MINH CITY - Văn Quảng, Lý; Kỳ Văn, Hạ; Đỗ Huy Hoàng, Nguyễn (Journal of Health and Aging, 2025)
Evaluation of the treatment outcomes of ureteral stones in super-elderly patients using retrograde ureteroscopic lithotripsy (URSL) at Thong Nhat Hospital, Ho Chi Minh City. A retrospective descriptive study was conducted on 68 patients aged 80 years and older who underwent URSL from January 2022 to January 2025. Data on patient characteristics, stone size and location, stone-free rates, operative time, hospital stay, complications, and factors affecting treatment outcomes were collected and analyzed. The mean age of patients was 83.7 ± 3.1 years, with 57.3% being male. The average stone size was 12.3 ± 3.8 mm; 36.8% of patients had stones larger than 1.5 cm, and 30.9% had stones located in the upper third of the ureter. The stone-free rate after the first ureteroscopic lithotripsy was 84.7%, which increased to 93.8% after the second session. However, 7.4% of patients still had residual stones, mainly due to difficult anatomical locations or ureteral edema. The mean operative time was 29.4 ± 9.7 minutes (range 19–48 minutes). Complications occurred in 12.1% of cases, most commonly urinary tract infection (5.8%), mild bleeding (2.9%), and minor ureteral injury (3.4%). The mean hospital stay was 7.2 ± 1.9 days. Retrograde ureteroscopic lithotripsy represents an effective and safe treatment modality in the super-elderly population, demonstrating high stone-free rates with an acceptable complication profile. However, individualized treatment planning is essential, particularly in cases involving large calculi, proximal ureteral stones, or significant underlying comorbidities.